Cenozoic exhumation on the southwestern Barents Shelf: Estimates and uncertainties constrained from compaction and thermal maturity analyses. (May 2016) - Baig, Irfan; Faleide, Jan Inge; Jahren, Jens; Mondol, Nazmul Haque
Abstract: The Barents Sea is believed to have been influenced in most parts by Cenozoic uplift and erosion episodes. The rocks in the area are not currently at their maximum burial depth. The exhumation of the sedimentary rocks has had large effects on rock physical properties and hydrocarbon maturation and migration. The current study seeks to estimate exhumation from shale compaction and thermal maturity techniques and discuss its implications for hydrocarbon exploration in the uplifted Barents Sea area. This study uses well logs and thermal maturity data together with widely distributed shot gather data along long-offset seismic reflection lines. The use of shale compaction techniques to estimate exhumation was focused particularly on the regionally preserved Aptian-Albian (Kolmule Formation) and Paleogene (Torsk Formation) shales. Normal compaction reference curves were established for these units in areas currently at their maximum burial depth (e.g. Sørvestsnaget Basin and Vestbakken Volcanic Province). The results suggest widespread Cenozoic exhumation throughout the southwestern Barents Sea. The exhumation magnitudes increase towards east and northeast. The average exhumation estimates from the three data sources range from ∼800 to 1400 m within the Hammerfest Basin, ∼1150–1950 m on the Loppa High, ∼1200–1400 m on the Finmark Platform and ∼1250–2400 m on the Bjarmeland Platform. The marked differences in glacial erosion from mass balance and average erosion estimates from the current study suggest a significant pre-glacial uplift and erosion in the southwestern Barents Sea area. The observed stratigraphy and presence of significant volumes of Late Oligocene-Middle Miocene sediments in basins at the outer margin, and increased erosion rates at the same time in source areas suggest that maximum burial in the southwestern Barents Sea may have occurred sometime during the Oligocene, or even earlier in the Eocene. The results from this study are useful input for modelling of source rock maturation, generation, migration and trapping of hydrocarbons in the area. These results are also an important input for the prediction of more precise reservoir and seal rock properties in frontier areas away from the exploration wells and provide valuable knowledge for the use of interval velocities in the uplifted areas.